MAKNA KEUANGAN NEGARA DALAM PASAL PASAL 23 E UNDANG-UNDANG DASAR 1945 - Laurensius Arliman S (Lex Librum : Jurnal Ilmu Hukum, 2020)
State finance is only interpreted narrowly, which is limited to the State Revenue and Expenditure Budget. Article 23 E of the 1945 Constitution states that in order to examine the management and responsibility of state finance, a free and independent Supreme Audit Agency (BPKP) is held. Based on the provisions of Article 6 of Law 17/2003, the President as the Head of Government holds the power of managing state finances as part of the next governmental power: authorized by the Minister of Finance, as fiscal manager and Government Representative in the ownership of separated state assets; authorized to the minister / head of the institution as the Budget User / Property User the state ministry / institution he leads; submitted to the governor / regent / mayor as head of regional government to manage regional finance and represent the regional government in the ownership of separated regional assets; and not including the authority in the monetary sector, which includes among other things issuing and circulating money, which is regulated by law. As the holder of the power of state financial management, the government has a supervisory agency / agency / unit within the government that has the duty and function of conducting supervision which is often known as the Government Internal Supervisory Apparatus consisting of the Financial and Development Supervisory Agency and Inspectorate General.